An improved FT-TIMS method of measuring uranium isotope ratios in the uranium-bearing particles. (December 2015) - Chen, Yan; Wang, Fan; Zhao, Yong-Gang; Li, Li-Li; Zhang, Yan; Shen, Yan; Chang, Zhi-Yuan; Guo, Shi-Lun; Wang, Xiao-Ming; Cui, Jian-Yong; Liu, Yu-Ang
Abstract: An improved method of Fission Track technique combined with Thermal Ionization Mass Spectrometry (FT-TIMS) was established in order to determine isotope ratio of uranium-bearing particle. Working standard of uranium oxide particles with a defined diameter and isotopic composition were prepared and used to review the method. Results showed an excellent agreement with certified values. The developed method was used to analyze isotope ratio of single uranium-bearing particle in swipe samples successfully. The analysis results of uranium-bearing particles in swipe samples accorded with the operation history of the origin. Highlights: The developed method was successfully applied in the analysis of real swipe sample. Uranium-bearing particles were confined in the middle of track detector. The fission tracks of collodion film and PC film could be confirmed each other. The thickness of collodion film should be no more than about 60 μm. The method could avoid losing uranium-bearing particles in the etching step.